Increasing the Efficacy of SLNB in Cases of Malignant Melanoma Located in Close Proximity to the Lymphatic Basin. (10th February 2014) - Bogdanov-Berezovsky, Alexander; Pagkalos, Vasileios A.; Silberstein, Eldad; Shoham, Yaron; Xanthinaki, Arsinoi A.; Krieger, Yuval
Abstract : Background. Being predictive of the entire nodal bed, sentinel lymph node biopsy (SLNB) is invaluable in the surgical management of melanoma. Although the concept is simple, sentinel lymph node (SLN) identification and removal can be technically challenging. Methods. A total of 102 consecutive patients have undergone SLNB in the Division of Plastic and Reconstructive Surgery of Soroka University Medical Center from 2009 to 2012. Patients have undergone SLNB using a radioactive tracer and blue stain in order to identify the SLN. Although SLNB usually precedes the wide excision of melanoma, primary lesions in close proximity (< 10 cm) to the lymph basin require wide excision before beginning the SLN quest. Results. All pathology reports confirmed the excision of lymph nodes. Conclusions. When treating MM in close proximity to the lymph basin, changing the sequence of the SLNB procedure seems to increase the efficacy of the method.